Nutritional quality improvement in maize (Zea mays): Progress and challenges - KUMAR, PARDEEP; CHOUDHARY, MUKESH; HOSSAIN, FIROZ; SINGH, N K; CHOUDHARY, POONAM; GUPTA, MAMTA; SINGH, VISHAL; CHIKAPPA, G K; KUMAR, RAMESH; KUMAR, BHUPENDER; JAT, S L; RAKSHIT, SUJAY (The Indian Journal of Agricultural Sciences, 2019)
Malnutrition is one of the important problems which affect the overall human productivity costing huge economic losses to the nations. Addressing malnutrition problem is one of the important components of sustainable development goals. In this context, biofortification of staple food crops could be one of the most practical, environment friendly, cost effective and sustainable approaches in the long run. Maize (Zea mays L.) being staple food crop for more than 900 million populations across the globe, enhancing the nutrient content along with yield is of paramount importance. Maize display large genetic diversity for all the quality parameters and several mutants are available each of the quality traits. Across the globe, several efforts have been made to identify new gene(s) and QTLs for different quality traits and their mobilization to develop new and improved biofortified cultivars. However, any technology or product remains meaningless unless it reaches the main stakeholders. The main stakeholders are the poorest of poor of the society who are most affected due to malnutrition. In order to make biofortification a success story, there is need to address several challenges like appreciated support price for the produce, dedicated production zones, value addition and supply chain development. The policy intervention with respect to sensitization on importance of nutrient rich cultivars and their acceptance by farmers, traders and consumers are the key to success.